Effect of Steam‐Treatment Time on the Length and Structure of Single‐Walled and Double‐Walled Carbon Nanotubes. Issue 2 (22nd December 2015) - Kierkowicz, Magdalena; Pach, Elzbieta; Santidrián, Ana; Tobías‐Rossell, Ester; Kalbáč, Martin; Ballesteros, Belén; Tobias, Gerard
Abstract: A major challenge to turn the potential of carbon nanotubes (CNTs) into customer applications is to reduce or eliminate their toxicity. Taking into account health and safety concerns, intensified research efforts have been conducted to improve the biocompatibility of CNTs, including the development of new shortening and purification strategies. Ideally, the methods used for improving the biocompatibility of CNTs should not alter the electronic properties of CNTs. Herein, we report on the shortening of a sample containing single‐walled and double‐walled CNTs using steam and obtain new insights in the properties of the steam‐treated CNTs. The present study shows that short CNTs (median length ca. 200 nm) can be obtained under the reported conditions. Raman analysis reveals that wider and outer nanotubes undergo more significant changes than the narrower and inner ones, especially after a prolonged steam treatment. Abstract : Steamed up : New insights on the role that steam plays in both the length distribution and electronic properties of carbon nanotubes are discussed. Short CNTs can be achieved after 10 h steam treatment with a median length of 200 nm. Raman analysis reveals that wider and outer nanotubes undergo more significant changes than the narrower and inner ones, especially after a prolonged steam treatment.